Factors Associated with Missed Vaccination during Mass Immunization Campaigns - Weiss, William M; Winch, Peter J; Burnham, Gilbert (Journal of Health, Population and Nutrition, 2009)
Achieving a high percentage of vaccination coverage with polio vaccine, while necessary, is not sufficient to eliminate or eradicate polio. The existence of pockets of under-vaccinated children has allowed outbreaks of polio in countries that have achieved high levels of vaccination coverage and in countries with no cases for many years. In a literature review, 35 articles were identified that described factors associated with missed vaccination in mass immunization campaigns. An annotated bibliography was developed for each article; these were then coded using the AnSWR program, and codes were organized into three larger thematic categories. These thematic areas were: (a) organization and implementation of mass campaigns; (b) population characteristics; and (c) knowledge and practices of caretakers. If these factors were geographically clustered, it was suspected that these clusters might have higher likelihood of becoming pockets of unvaccinated children. Immunization programme managers can target resources to identify if such clusters exist. If so, they can then ensure supervision of vaccination efforts in those sites and take further action, if indicated, to prevent or mitigate pockets of unvaccinated children. Key words: Child health; Evaluation studies; Immunization; Polio; Polio vaccine; Review literature; Vaccine doi: 10.3329/jhpn.v27i3.3378 J Health Popul Nutr 2009 Jun;27(3):358-367